Persistency in Malaysian higher education - Mosaku, Monsurat Olusola (2010)
Higher Education (HE) is becoming an increasingly complex phenomenon throughout the world due to observable major contemporary trends such as diversification, privatization, globalization and internalization. Higher Education Institutions which were originally for the elites are now accessible to the diverse populace to the extent of open (universal) admission policy in some countries. Diversification and its resultant massification has good intent but with attendant negative repercussions. Most notable of the later are reduced government funding, shift in purpose from a public good to private good and less academic autonomy. The effects of the afore mentioned are weak admission policy, quality control problems, and persistency on the part of the students amongst others. Persistency is the situation in which students are still in enrolment at some predetermined point(s) in time following either commencement or attendance. The aim of this paper is to investigate one of the effects of diversification that is persistency in the Malaysian context as a voluminous amount of research has been carried out in the developed world but the issue has not been adequately addressed in Malaysia.